The Law Relating to Satellite Navigation and Air Traffic Management Systems - A View from the South Pacific - Murray, Kim (Victoria University of Wellington Law Review, 2000)
This article is an updated and revised version of a paper originally presented to a Communication, Navigation, Surveillance/ Air Traffic Management Forum of Pacific state, airline and air traffic service provider organisation representatives meeting in Sydney, Australia on 16 April 1998. The Forum was organised under the auspices of the Australian Branch of the Royal Aeronautical Society.